Rent Control: An Economic Abomination - Block, Walter (International journal of value-based management, 1998)
Rent control is a public policy which fails on both normative and positive economic grounds. In the former case, it violates all canons of equity, of both right (private property rights are sacrosanct) and left (it does not promote egalitarianism, rather, often, it enriches rich tenants and impoverishes poor landlords). In the latter, it leads to inefficiency, deterioration of rental housing, reduces incentives for upkeep and maintenance, reduces labor mobility, exacerbates landlord tenant relations, promotes housing abandonment and homelessness, and misallocates resources away from residential rental units. This sovietization of housing has effects similar to the sovietization of anything else: farming, factories, industry, forestry, whatever.